2013
DOI: 10.1021/ic400576m
|View full text |Cite
|
Sign up to set email alerts
|

A Versatile Diphosphine Ligand: cis and trans Chelation or Bridging, with Self Association through Hydrogen Bonding

Abstract: The diphosphine ligand, N,N'-bis(2-diphenylphosphinoethyl)isophthalamide, dpipa, contains two amide groups and can form cis or trans chelate complexes or cis,cis or trans,trans bridged complexes. The amide groups are likely to be involved in intramolecular or intermolecular hydrogen bonding. This combination of properties of the ligand dpipa leads to very unusual structural properties of its complexes, which often exist as mixtures of monomers and dimers in solution. In the complex [Au2(μ-dpipa)2]Cl2, the liga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 70 publications
0
16
0
Order By: Relevance
“…Hydrogen bonding (H-bonding) plays numerous important roles in the biology. , In particular, many metalloenzymes harness hydrogen bonds (H-bonds) in bringing, holding, and orienting a substrate closer to the active site, a critical step before the actual function or transformation. , Appreciable attention has been given to install H-bonding functional groups in synthetic systems. Successful examples include the stabilization of unusual species and intermediates ,, and effective control of the reaction outcome. , H-bonding and other weak interactive forces have also been utilized for preorganizing substrates during the catalysis . Such interactions have elegantly assisted both in regio- and enantioselective catalysis by holding a substrate closer to a catalytic site. A few supramolecular metal–ligand assemblies have also been found to aid in catalysis by stabilizing cavity-encapsulated substrates and reagents .…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen bonding (H-bonding) plays numerous important roles in the biology. , In particular, many metalloenzymes harness hydrogen bonds (H-bonds) in bringing, holding, and orienting a substrate closer to the active site, a critical step before the actual function or transformation. , Appreciable attention has been given to install H-bonding functional groups in synthetic systems. Successful examples include the stabilization of unusual species and intermediates ,, and effective control of the reaction outcome. , H-bonding and other weak interactive forces have also been utilized for preorganizing substrates during the catalysis . Such interactions have elegantly assisted both in regio- and enantioselective catalysis by holding a substrate closer to a catalytic site. A few supramolecular metal–ligand assemblies have also been found to aid in catalysis by stabilizing cavity-encapsulated substrates and reagents .…”
Section: Introductionmentioning
confidence: 99%
“…Phosphinocarboxylic amides , are versatile ligands for coordination chemistry and catalysis. Their attractiveness results mainly from their hybrid-donor character and modular structures, which allow for fine tuning to the intended purpose.…”
Section: Introductionmentioning
confidence: 99%
“…61−65 Such paucity is related to the difficulty in first synthetically installing H-bonds followed by giving them the required orientations to interact with an analyte of choice while also avoiding their undesirable interactions with lattice solvent molecules and/or anions. 61,62 Although there have been a few examples where H-bonds have been incorporated within coordination-driven self-assemblies, in most cases Hbonds have been primarily used for structural purposes rather than focusing on their influence on applications. 61−63 Our research group has recently reported two Pd(II) macrocycles synthesized using pyridine-2,6-dicarboxamide based ligands offering appended phosphine groups.…”
mentioning
confidence: 99%
“…Such a fact is not only related to the presence of well-defined cavities such molecular assemblies offer but also due to the possibility to fine-tune these cavities. Several such molecular assemblies have been effectively used in host–guest chemistry, sensing, drug delivery, stabilizing reactive intermediates , and organic transformations. Extensive efforts have been made to synthesize assorted molecular assemblies that show remarkable properties. , Efforts vary from the construction of molecular assemblies offering hydrophobic interior space, and examples include various covalent bonding based assemblies with the objective to tune the cavity structure to suit an application. Efforts have also been made to construct metal–ligand coordination driven molecular assemblies that rely on the geometrical parameters of both metal(s) and ligand(s). In such molecular assemblies, the interior space has been designed to offer hydrophobic , as well as hydrophilic functional groups. In contrast, examples are scarce when hydrogen bonds (H-bonds) are installed within a cavity. Such paucity is related to the difficulty in first synthetically installing H-bonds followed by giving them the required orientations t...…”
mentioning
confidence: 99%